Eksplorasi Bakteri Penambat Nitrogen dari Tanah Hutan Mangrove Sungai Peniti, Kabupaten Mempawah - Rafdinal, Kabul Santoso, Rahmawati (Jurnal Protobiont, 2019)
Peniti Mangrove Forest is one of the forests in West Kalimantan that has high forest productivity, thus supporting the presence of nitrogen-fixing bacteria. Nitrogen fixing bacteria is one of the nitrogen-fixing microorganisms that can bind the free nitrogen needed for the nitrogen cycle process. This study aimed to determine the types of nitrogen-fixing bacteria that can be found in the soil of Peniti mangrove forest, Mempawah Regency, West Kalimantan. Taking soil samples used a purposive sampling method. Bacterial isolation used dilution techniques and pour plate method on the Nitrogen Free Bromthymol Blue (NFB) media. The nitrogen fixing was obtained by 3 isolates of nitrogen fixing bacteria. After identification, 3 genera were obtained, namely members of the genera Azotobacter, Azospirillum, and Pseudomonas.